Cyclophosphamide‑induced hepatotoxicity in Wistar Rats: the modulatory role of Gallic Acid as a hepatoprotective and Chemopreventive phytochemical (2016)
Background: Gallic acid (GA) is an endogenous plant phenol known to have antioxidant, free radical scavenging ability, anti‑inflammatory, anti‑cancer, and anti‑fungal properties. The aim of this study was to assess the protective effect of GA on cyclophosphamide (CPA)‑induced hepatotoxicity in male Wistar rats. Methods: Sixty rats were grouped into six groups of 10 rats per group. Group 1 received distilled water. Group 2 received CPA at 200 mg/kg single dose intraperitoneally on day 1. Groups 3 and 4 received a single dose of CPA (200 mg/kg) intraperitoneally on day 1 and then were treated with GA at 60 and 120 mg/kg body weight for 14 days, respectively. Rats in Groups 5 and 6 only received GA at 60 and 120 mg/kg body weight for 14 days, respectively. GA was administered orally. Results: CPA induced hepatic damage as indicated by significant elevation (P < 0.05) in aspartate aminotransferase, organ weight, and evidence by the histological study. CPA also induced hepatic oxidative stress as indicated by significant elevation (P < 0.05) in malondialdehyde content, hydrogen peroxide (H2O2) generation, nitrite level, and the level of glutathione (GSH) peroxidase crashed in the CPA‑treated group. GA enhanced the antioxidant defense system as indicated by significant elevation (P < 0.05) in GSH level, catalase activity, and GSH‑S‑transferase activity. Conclusions: Taken together, the result of this present study shows that GA has a protective effect on CPA‑induced hepatotoxicity.